2010
DOI: 10.1051/limn/2010016
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Ostracoda (Crustacea) of Inari Lapland in northern Finland

Abstract: -Collections of ostracods from various habitats in and around Lake Inari, Finnish Lapland, provide the first record of these crustaceans from Finland north of the Arctic Circle. From a total of 35 sites visited, 14 species were collected, out of which four appeared to be new to Finland: Fabaeformiscandona lapponica, Pseudocandona pratensis, Eucypris pigra and Paralimnocythere relicta. Two major assemblage groups were recognised by clustering classification and multi-dimensional scaling ordination, one dominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Although we noted three assemblage types we found that the average mutual Bray-Curtis similarity between the site assemblages was relatively low. our previous research on the ostracod fauna of Inari Lapland (Iglikowska and Namiotko, 2010) and our comparison with the ostracod fauna of Poland (Iglikowska and Namiotko, in press), revealed that all Lapponian assemblages are drawn from a single coherent assemblage type, regardless of habitat type. Dominance of any one of the three mentioned species may simply reflect factors such as the timing of colonization of the habitat.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…Although we noted three assemblage types we found that the average mutual Bray-Curtis similarity between the site assemblages was relatively low. our previous research on the ostracod fauna of Inari Lapland (Iglikowska and Namiotko, 2010) and our comparison with the ostracod fauna of Poland (Iglikowska and Namiotko, in press), revealed that all Lapponian assemblages are drawn from a single coherent assemblage type, regardless of habitat type. Dominance of any one of the three mentioned species may simply reflect factors such as the timing of colonization of the habitat.…”
Section: Discussionsupporting
confidence: 48%
“…2). Iglikowska and Namiotko (2010) found no significant correlation between habitat type and ostracod species composition in Lapland. In the current study the most noticeable change from the beginning of the 20 th century seems to be a retreat of the Arctic species C. laciniata and T. glacialis in Lapland.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations